2003
DOI: 10.1097/01.sla.0000089855.96280.4a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surgical Subspecialty Training on In-Hospital Mortality for Gastrectomy and Colectomy Patients

Abstract: For gastrectomies and colectomies, risk-adjusted mortality is substantially lower when performed by subspecialty interested and trained surgeons, even after accounting for hospital and surgeon volume and patient characteristics. These findings may have implications for surgical training programs and for regionalization of complex surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 15 publications
3
75
0
4
Order By: Relevance
“…With the introduction of the pathway, patients in this group had gastrectomies performed only by two sub-specialist upper gastrointestinal surgeons [14]. This change of practice in our unit may have affected the operative standards, as suggested by the increased extent of lymph node dissection (mostly D2) in the pathway group [15]. However, extended nodal dissection may increase the risk of postoperative complications, which would favor the results of the pre-pathway group.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of the pathway, patients in this group had gastrectomies performed only by two sub-specialist upper gastrointestinal surgeons [14]. This change of practice in our unit may have affected the operative standards, as suggested by the increased extent of lymph node dissection (mostly D2) in the pathway group [15]. However, extended nodal dissection may increase the risk of postoperative complications, which would favor the results of the pre-pathway group.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of subspecialization in surgery is also backed by a series of Western studies, such as the study by Callahan et al [21], in which it was concluded that the adjusted mortality risk was substantially lower when gastrectomies were performed by trained subspecialized surgeons. Additionally, Western centers that have adopted working systems of this type and have recognized the learning curve for the D2 lymphadenectomy have shown great improvement in their results, which are similar to those of the Japanese studies; for example, Lewis et al [22] found that surgical subspecialization reduced operative mortality from 12% to 3.1% over a period of 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the non‐elective admission rate was higher in very‐low‐volume hospitals than in very‐high‐volume hospitals (51.4% vs 29.7%), and that this discrepancy was possibly associated with a difference in mortality rates (13.0% vs 8.7%). A significant correlation between hospital volume and postoperative mortality was also observed in six studies in the USA 16, 17, 18, 19, 20, 21 and three studies in Europe 22, 23, 24. Among eight other large‐scale studies, only one could not show a significant relationship between higher hospital volume and lower hospital mortality, but the absolute difference in mortality between low‐ and high‐volume hospitals was greater than 1% (8.7% vs 6.9%) 25…”
Section: Resultsmentioning
confidence: 58%